Albumin use in patients with septic shock-Post-hoc analyses of an international randomised fluid trial - Meyhoff, Tine Sylvest; Granholm, Anders; Hjortrup, Peter Buhl; Sivapalan, Praleene; Lange, Theis; Laake, Jon Henrik; Cronhjort, Maria; Jakob, Stephan M; Cecconi, Maurizio; Nalos, Marek; Ostermann, Marlies; Malbrain, Manu L N G; et al. (Acta anaesthesiologica Scandinavica, 2024)
BACKGROUND: Albumin administration is suggested in patients with sepsis and septic shock who have received large volumes of crystalloids. Given lack of firm evidence, clinical practice variation may exist. To address this, we investigated if patient characteristics or trial site were associated with albumin use in septic shock. METHODS: We conducted a post-hoc study of the CLASSIC international, randomised clinical trial of fluid volumes in septic shock. Associations between selected baseline variables and trial site with albumin use during ICU stay were assessed in Cox models considering death, ICU discharge, and loss-to-follow-up as competing events. Baseline variables were first assessed individually, adjusted for treatment allocation (restrictive vs. standard IV fluid), and then adjusted for allocation and the other baseline variables. Site was assessed in a model adjusted for allocation and baseline variables. RESULTS: We analysed 1541 of 1554 patients randomised in CLASSIC (99.2%). During ICU stay, 36.3% of patients in the restrictive-fluid group and 52.6% in the standard-fluid group received albumin. Gastrointestinal focus of infection and higher doses of norepinephrine were most strongly associated with albumin use (subgroup with highest quartile of norepinephrine doses, hazard ratio (HR) 2.58, 95% CI 1.89 to 3.53). HRs for associations between site and albumin use ranged from 0.11 (95% CI 0.05 to 0.26) to 1.70 (95% CI 1.06 to 2.74); test for overall effect of site: p < .001. CONCLUSIONS: In adults with septic shock, gastrointestinal focus of infection and higher doses of norepinephrine at baseline were associated with albumin use, which also varied substantially between sites.
Keywords: dospělí; sepse; Sepsis; septický šok; lidé; noradrenalin; albuminy; tekutinová terapie; Shock, Septic; Albumins; Fluid Therapy; Adult; Norepinephrine; Humans